Makna Citra Diri dalam Pengalaman Body Shaming Online - Ainaya Al Fatimah; Nadya Ariyani Hasanah Nuriyyatiningrum; Ikhrom Ikhrom (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to understand how individuals perceive and experience body shaming on social media, its impact on self-image, and the coping strategies employed in response. Using a qualitative approach, data were collected through an open-ended online questionnaire completed by 20 participants aged 18 to 22 years, consisting of 70% females and 30% males. The data were analyzed using thematic analysis to identify patterns in experiences, perceptions, and psychological responses to body shaming. The results indicate that most participants interpret body shaming as a form of verbal abuse rooted in narrow societal standards of the ideal body. Reported psychological impacts include decreased self-confidence, anxiety, and changes in online behavior, although some participants demonstrated resilience by employing coping strategies such as self-acceptance, lifestyle changes, and seeking social support from family and friends. The study also reveals that body shaming occurs not only in public digital spaces like TikTok and Instagram but also in private digital settings such as WhatsApp groups. These findings underscore the need for educational interventions, strengthened support from families and schools, and the development of protective digital policies and features to address verbal abuse on social media.